Establishing harmonic distortion level of distribution network based on stochastic aggregate harmonic load models - Au M.T.; Milanovi? J.V. (2023)
This paper presents a stochastic aggregate harmonic load (AHL) model built from physical load parameters. Parameters used include nonlinear load composition, diversity factors, and nonlinear load participation in total demand. They are obtained from samples of customer load database of different sectors of customers. The aggregate load modules are developed for harmonic simulation of distribution network using commercially available software. Uncertainties in loading conditions, load composition and aggregate harmonic load parameters are taken into account separately and simultaneously to determine voltage harmonic distortion levels in distribution network. The simulations performed on a large, realistic distribution network using developed AHL modules give realistic voltage distortion levels/ranges. The results of simulations are in agreement with field measurement results. 2007 IEEE.